Effect of Copper doped and Magnesium co-doped BiFeO3 for photocatalytic activity - Rajitha Beerelli; Padma Suvarna (Journal of Water and Environmental Nanotechnology)
In this current research work, the synthesis of Copper (Cu) doped and Magnesium (Mg) co-doped of BeFiO3 (BFO), i.e BiFe1-xCuxO3 (where; X= 0.1, 0.15 and 0.2 wt.%) and Bi1-yMgyFe1-xCuxO3 (where; Y=0.05, 0.1 and 0.15 wt.%) were prepared by sol-gel method. The obtained samples were analyzed by various characterization techniques including X-ray diffraction (XRD), surface morphology examined by field emission scanning electron microscopy (FE-SEM) and transition electron microscopy (TEM). It was noted that Cu (0.15 wt.%) doped BFO had notable photocatalytic activity for Rhodamine (RhB) dye degradation when exposed to visible light irradiation. In addition to Cu (0.15 wt.%) by adding Mg (0.1 wt.% ) as a co-doping, exhibited higher photodegradation than the pure BFO, Cu-doped BFO (0.1and 0.2 wt.%) and Mg co-doped BFO (0.05 and 0.15 wt.%). Here we reported a new driven photocatalyst by doping of Cu and co-doping of Mg into BFO simultaneously. These played a key role in hampering the recombination of electron-hole pairs hence chance to increase dye degradation performance. These findings could be useful for developing affordable photocatalysts for wastewater purification.